Visible light-responsive composition-dependent morphology and cargo release in mixed micelles of dendron amphiphiles - Avhad, Shankarrao V.; Kumar, Sugam; Ambade, Ashootosh V. (Langmuir, 2025)
2,2-Bis-(methylol)propionic acid-based second-generation polyester dendron amphiphile (T-D) containing visible light-responsive donor-acceptor Stenhouse adduct (DASA) as hydrophobic tails is synthesized. Micelles of T-D amphiphile and its mixed micelles of varying compositions with nonresponsive dendron amphiphile containing lauryl groups are prepared in aqueous solution. In transmission electron microscopy and atomic force microscopy analyses, T-D amphiphiles show rice grain-like ellipsoidal micelles as the predominant morphology. Mixed micelles display a composition-dependent morphology gradient such that the morphology changes from rice grain like to mixed to completely spherical with decreasing content of the T-D amphiphile. Complete morphology change to spherical micelles and partial reversal to ellipsoidal micelles, finally leading to ill-defined aggregates, are observed when the T-D amphiphile micelles are subjected to visible light-dark storage photoswitching cycles. Small-angle neutron scattering (SANS) analysis of 1 wt.% micellar solution in THF:water (10:90) reveals only a minor change in shape and size upon photoirradiation, and the data could be fitted to spherical or ellipsoidal model. Release of hydrophobic dye from mixed micelles is tuned by the content of the photoresponsive amphiphile. Cellular uptake and visible light-triggered release of hydrophobic drug from mixed micelles are demonstrated using MDA-MB-231 cells, suggesting their applicability for photoresponsive drug delivery.